2018
DOI: 10.1186/s13054-018-2222-7
|View full text |Cite
|
Sign up to set email alerts
|

Endocan, sepsis, pneumonia, and acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) and hospital-acquired pneumonia (HAP) are major problems of public health in intensive care units (ICUs), occurring in 15% of critically ill patients. Among the factors explaining ARDS development, sepsis is known as a frequent cause. Sepsis, ARDS, and HAP increase morbidity, mortality, length of stay in the ICU, and the overall costs of healthcare. The major challenge remains to identify accurately among critically ill patients those at risk of poor outcomes who coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 63 publications
1
56
0
1
Order By: Relevance
“…Through binary logistic regression analysis, it was found that ESM-1, CRP and IL-6 amounts on Day 1 were independently associated with ARDS occurrence in sepsis patients. ROC curve analysis showed that Day 1's plasma ESM-1 (AUC = 0.75) was superior to CRP (AUC = 0.736) and IL-6 (AUC = 0.736) in predicting the occurrence of ARDS within 72 hours, in agreement with De Freitas et al [26] .With a cutoff plasma ESM-1 levels of 5.865 ng/mL, the sensitivity and speci city of this parameter were 0.786 and 0.583, respectively, in predicting ARDS occurrence in sepsis patients. The accuracy in predicting ARDS occurrence was relatively high, with a low rate of missed diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Through binary logistic regression analysis, it was found that ESM-1, CRP and IL-6 amounts on Day 1 were independently associated with ARDS occurrence in sepsis patients. ROC curve analysis showed that Day 1's plasma ESM-1 (AUC = 0.75) was superior to CRP (AUC = 0.736) and IL-6 (AUC = 0.736) in predicting the occurrence of ARDS within 72 hours, in agreement with De Freitas et al [26] .With a cutoff plasma ESM-1 levels of 5.865 ng/mL, the sensitivity and speci city of this parameter were 0.786 and 0.583, respectively, in predicting ARDS occurrence in sepsis patients. The accuracy in predicting ARDS occurrence was relatively high, with a low rate of missed diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…These experimental data con rmed that low plasma ESM-1 levels in sepsis patients may be associated with ARDS occurrence. It is generally admitted [26,27] that ESM-1 secreted by endothelial cells protects lung injury by reducing the adhesion of white blood cells to endothelial cells. ESM-1 can bind to LFA-1 to prevent its interaction with ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Sepsis generally initiates a systemic inflammatory response, and proinflammatory cytokines, such as tumor necrosis factor alpha, interleukin 1 beta (IL-1β), IL-6, and IL-8, 32 , 33 are released. These cytokines activate neutrophils to produce toxic mediators and damage the endothelium and alveolar epithelium, 34 36 eventually leading to alveolar–capillary barrier injury. 30 , 37 Then, the protein-rich fluid induces acute pulmonary edema and inactivates PS.…”
Section: Discussionmentioning
confidence: 99%
“…Endocan is a diagnostic and prognostic biomarker for sepsis and acute respiratory distress syndrome [9]. CRRT with a membrane cut-off of 35 kDa is unlikely to remove endocan (MW 40 kDa), but removal may possibly occur by adsorption when HAMs are used [10].…”
Section: Biomarkers Not Eliminated By Crrt or Sorbents But Needing Fumentioning
confidence: 99%